Self expression and authenticity in Mohan Hazian’s personal communication through the book “Goresan Seorang Berandal” - Maskuri, M. Ibnu Naufal (Privietlab, 2026)
This study looks at how Mohan Hazian shows himself and stays true to who he is through his book